Prefiksoidne zloženke ali besedne zveze med slovarjem, normo in korpusno rabo - Brkić, Nikolina; Nadelsberger, Lora; Stramljič Breznik, Irena (Revija za elementarno izobraževanje, 2016)
Prefixoid Compounds or Phrases between the Dictionary, Standard Rules and Corpus Use. The article looks into the recommendations for writing bio, mobi, tehno and turbo as elements of words or phrases in the normative orthography manual. It parallels these with the writing practice in the more recent general dictionaries, as well as with the actual use in the Gigafida and Kres text corpora. The data regarding their writing in the corpora is compared to the recommendations from the current polemics, which prefers the semantic scale to the formal one.
Keywords: phrase; prefix compounds; writing together or apart; norm; use